Mechanistic insights into sulfur rich oil formation, relevant to geological carbon storage routes. A study using (+) APPI FTICR-MS analysis. (September 2020) - Silva, Renzo C.; Yim, Calista; Radović, Jagoš R.; Brown, Melisa; Weerawardhena, Priyanthi; Huang, Haiping; Snowdon, Lloyd R.; Oldenburg, Thomas B.P.; Larter, Steve R.
Highlights: Lipids with ≤6 S atoms have been detected as free molecules in sulfur rich oils. Immature sulfur rich oils contain S-steroids, -hopanoids, -carotenoids, -alkenones. (+) APPI CID-FTICR-MS indicated only minor thiols and sulfide bridges. Precursor and sulfurized products relationships are clarified. Some geoengineering paths to carbon sequestration require such understanding. Abstract: Sulfur incorporation into sedimentary organic matter has a key role in carbon preservation in the geosphere. Such processes can inform strategies for human timescale carbon storage to mitigate climate change impacts and thus more detailed knowledge of sulfur incorporation into biomass species is needed. Until recently, detailed chemical characterization of sulfurized organic matter was only possible by analyzing individual building blocks obtained after desulfurization reactions. In this study, Fourier transform ion cyclotron resonance mass spectrometry (FTICR-MS), with atmospheric pressure photoionization in positive ion mode, (+) APPI, was used to investigate the chemical composition of sulfur rich crude oils and to obtain mechanistic insights into the sulfur incorporation reactions happening during early diagenesis. Contrary to expectations, (+) APPI FTICR-MS data show that sulfurized lipids (with up to 6 sulfur atoms and up to m / z 1100) occur as free molecules in these oils, rather than within a macromolecular network linked by (poly)sulfide bridges. In contrast to the mature Peace River (Canada) oils, the thermally immature Rozel Point (USA) and Jianghan Basin (China) oils show a carbon number preference in sulfurized species resembling biogenic precursor molecules, which highlights the importance of S-bound molecules as geochemical proxies for early diagenetic processes. This study indicates that sulfur incorporation reactions involve the formation of S-cyclic structures in which the double bond equivalent is ≥ the number of S atoms. Collision induced dissociation (CID-) FTICR-MS experiments suggest the occurrence of intermolecular sulfur incorporation reactions, but only as a mechanism that is secondary to intramolecular sulfur addition. The CID-FTICR-MS experiments indicated that steroid sulfurization typically yields S-bearing cyclic structures and that thiol/thioether groups may be present throughout the chemical matrix but only to a minor extent. In addition, CID-FTICR-MS also confirms the occurrence of sulfurized alkenones in low maturity oils. Knowledge of organic sulfur molecule formation informs routes for carbon dioxide removal technologies that could be used to sequester carbon in the geosphere and/or hydrosphere in the form of recalcitrant organic species.